Sustainability of Palm Sugar Home Industry Management in Rambah District, Rokan Hulu Regency - ., Albafery; ., Sukendi; ., Zulkarnain; ., Yusmarini (Journal of Ecohumanism, 2024)
The palm sugar industry in Rokan Hulu Regency, Indonesia, is a prominent agro-industry operating at a household level and mainly relies on raw palm sap. This study assesses the sustainability of the industry by analyzing its ecological, economic, social, legal/institutional, and technological dimensions. Using Multi-Dimensional Scaling (MDS) and participatory prospective analysis, findings indicate moderate sustainability in all dimensions except for legal/institutional aspects, which require improvement. Practical recommendations focus on institutional support, adoption of agroforestry, digital literacy, and women empowerment to enhance the industry’s resilience and adaptability. These recommendations aim to facilitate long-term sustainability by strengthening community involvement and integrating modern technology. The outcomes contribute to broader insights on managing small-scale agro-industries sustainably within rural communities.